Forced Internationalization of Higher Education: An Emerging Phenomenon - Ergin, Hakan; de Wit, Hans; Leask, Betty (International Higher Education, 2019)
A growing number of forced migrants are knocking on the doors of universities today. This paper argues that it is time for universities across the world to increase their efforts to provide access to higher education to forced migrants. Welcoming international disadvantaged groups into higher education is not only consistent with the traditional four rationales for internationalization (academic, sociocultural, political, and economic), it is also important for humanitarian reasons. Using the example of “forced migrants” from Syria in Turkey, we can see that this new phenomenon of “forced internationalization” creates uncommon challenges for institutions on a scale never seen before. However, it also creates opportunities for institutions and national systems seeking to internationalize, as well as for the many displaced scholars and students in the world today.